Synthesis, docking, ADMET prediction, cytotoxicity and antimicrobial activity of oxathiadiazole derivatives. (December 2018) - Yadav, Madhu; Srivastava, Ritika; Naaz, Farha; Singh, Ramendra K.
Graphical abstract: Highlights: New oxathiadiazoles designed and synthesized as potential antimicrobial agents. The molecules docked within the active site of PDF enzyme (PDB ID: 1G2A). Docking studies indicated about stable ligand-protein complexes. Antimicrobial activity determined using micro serial dilution method and cytotoxicity using MTT assay. Abstract: A series of molecules bearing oxathiadiazole, a five membered heterocyclic ring has been designed, synthesized and screened for antimicrobial activity. Molecules, 1a, 1b, 1d, 3a-b and4a-b were found to be highly active (MIC value upto 1.5 μg/mL) against different human pathogens, namely S. aureus, B. cerus, P. aeruginosa and E. coli. Some of the compounds, 1a, 1b and1d have also shown the antifungal activity (MIC value upto 6.2 μg/mL) against Candida albicans, Candida glubrate and Candida crusei . During in vitro cytotoxicity study, the oxathiadiazole derivatives showed less toxicity than the reference used against PBM, CEM and Vero (African green monkey kidney) cell lines. Docking studies suggested that all designed ligands interacted well within active site of PDF enzyme (PDB ID: 1G2A). Oxathiadiazole ring of all ligands formed H-bond with amino acid Leu91 at a distance ranging between 2.5–2.8 Å and also exhibited π - + and π - π interactions with amino acid residues Arg97 and His132, respectively. In silico ADMET evaluations of compounds showed more than 90% intestinal absorption for all compounds except4b (87.45%), which too was greater than the reference drugs sulfamethoxazole (76.46%) and chloramphenicol (69.94%). TOPKAT results also supported the lower cytotoxicity of all compounds.